2009
DOI: 10.1590/s0004-282x2009000400004
|View full text |Cite
|
Sign up to set email alerts
|

General practice physician knowledge about headache: evaluation of the municipal continual medical education program

Abstract: Improvement in post-CME scores confirms that the program had a significant immediate impact on the PCPs knowledge directly affecting the patient's health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…[18][19][20] In addition, although a few center exceptions do exist where the treating physicians had to discuss all first-time patients with their preceptors, had to discuss the follow-up consultations whenever the headache frequency reduction was not meaningful, and nearly 70% of the patients received the combination of pharmacological agents either for prevention as well as for the attacks, the pharmacological treatment of migraine in Brazilian public centers is inadequate and unsatisfying. 6,[21][22][23][24][25] Moreover, it may be suggested that the chronic form of migraine is even more undertreated in these instances. 6,22,25 As for the private tertiary centers, a combination of 2 pharmacological agents either for prevention as for the acute treatment was the most typically observed approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20] In addition, although a few center exceptions do exist where the treating physicians had to discuss all first-time patients with their preceptors, had to discuss the follow-up consultations whenever the headache frequency reduction was not meaningful, and nearly 70% of the patients received the combination of pharmacological agents either for prevention as well as for the attacks, the pharmacological treatment of migraine in Brazilian public centers is inadequate and unsatisfying. 6,[21][22][23][24][25] Moreover, it may be suggested that the chronic form of migraine is even more undertreated in these instances. 6,22,25 As for the private tertiary centers, a combination of 2 pharmacological agents either for prevention as for the acute treatment was the most typically observed approach.…”
Section: Discussionmentioning
confidence: 99%
“…6,[21][22][23][24][25] Moreover, it may be suggested that the chronic form of migraine is even more undertreated in these instances. 6,22,25 As for the private tertiary centers, a combination of 2 pharmacological agents either for prevention as for the acute treatment was the most typically observed approach. The pharmacological classes of neuromodulators, tricyclic antidepressants, and β-blockers were mostly used for prevention, whereas triptans and nonsteroidal anti-inflammatory drugs were mostly prescribed for headache attacks, as would be expected for headache specialists acting in tertiary centers.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 O importante é que cada situação merece uma atitude individualizada e ferramentas não faltam para desenvolver projetos de educação.…”
Section: Discussionunclassified
“…People with migraine typically present in primary healthcare settings, 3,5 with most remaining in primary care rather than being treated at tertiary or specialized headache clinics 5 . Previous studies have investigated the feasibility and effectiveness of different clinician education modalities (eg, face‐to‐face continuing medical education, distribution of resources, multifaceted workshop/lecture/supervised practice approach) to improve migraine diagnosis and management in primary care, 6‐8 showing variable degrees of success with clinician education. These studies, however, have exclusively involved primary care physicians (eg, general medical practitioners).…”
Section: Introductionmentioning
confidence: 99%